Effect of Some Materials on Productivity and Activity of -Hemolysin which Produced by Methicillin Ressistant Staphylococcus Aureus - Khalaf, Khawlah Jebur; Ali, Zainab Farhan (Iraqi Journal of Science, 2023)
In this study 77 human isolates of Staphylococcus aureus were obtain from different clinical sources. The results showed that the number of isolates producing α-hemolysin was 32 isolates (41.55%) , while non- hemolysin producing was 45 isolates (58.45%) .The minimum inhibitory concentration (MIC) of methicillin which were 32 micrograms ml. The effect of CD-Cholesterol ,Cholesterol ,Cyclodextran(CD) ,Methicillin and Phosphate Buffer Saline(PBS) on α- hemolysin activity was study and the hemolytic Titer was:8 ، 32.768 ,65.536 ,140.737.488.355.32 , 4.961408E + 25 respectively, while the effect of the same effect with Titer 67.108.864 and low Titer with PBS 3.96140812E + 25. The α – hemolysin toxin was partialy purified by ammonium sulfate precipitation. partial purified toxin was injected inside the cornea of rabbit’s eye and the erosion of cornea formed with diameter: 8 mm after 8 hours of injection while the erosion of cornea which injected with CD-Cholesterol that mixed with partial purified toxin was 4 mm. CD-Cholesterol was used in treatment as a drops which added to the affected eye and led to a decrease in corneal erosion area from 8 mm to 4 mm.